Alliance Israelite Universelle Schools within the existing school networks in the Ottoman Empire - Şar, Onur. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
This thesis examines the different schooling networks which were active in the Ottoman territories throughout the nineteenth century, with a specific focus upon the schools which were established by the Alliance Israélite Universelle. Highly influenced by the ideas of French Revolution and modernization, the organization which was instituted by a number of French Jews, inaugurated several schools for Ottoman Jewish communities at several localities. The primary aim of the association was to help oriental Jews to become like their European brothers. Their schools within Ottoman boundaries, thus, used to offer instruction with such a perspective. The aim of this thesis is realized through a number of primary and secondary sources, but its main contribution has been the integration of Ottoman archival materials into the topic. Together with other primary and secondary source materials, by the way of comparison, it was concluded that although Alliance schools may be labeled as foreign institutions on the basis of the fact that they were not under the jurisprudence of Ottoman Chief Rabbinate, in fact they differ from foreign schools in many ways. Furthermore, when the motive of establishment of foreign schools is taken into consideration, Alliance schools can be located in a limbo-like position between the schools established by foreign organizations and the community schools, which were under jurisprudence of millet başıs.|Keywords: Ottoman Empire, history of education, Alliance Israélite Universelle, schools, foreign schools, missionary schools, the nineteenth century
Keywords: Education -- Turkey -- History -- 19th century.